2016
DOI: 10.1007/s12288-016-0702-y
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Lymphoma Misdiagnosed as Pneumonia

Abstract: Pulmonary lymphoma is a very rare cause of lung tumors which occurs in less than one percent of primary malignant lung tumors. When seemingly pneumonia does not respond to treatment, the possibility of malignant lymphoma should always be considered. Here, we report two cases of pulmonary lymphoma misdiagnosed as pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 2 publications
2
4
1
2
Order By: Relevance
“…This type of PPL often accompanied with sign of air bronchogram, and bronchiectatic changes in our study and previously reported ( 6 , 9 , 14 ). Additionally, anti-inflammatory treatment is ineffective to PPL.…”
Section: Resultssupporting
confidence: 87%
“…This type of PPL often accompanied with sign of air bronchogram, and bronchiectatic changes in our study and previously reported ( 6 , 9 , 14 ). Additionally, anti-inflammatory treatment is ineffective to PPL.…”
Section: Resultssupporting
confidence: 87%
“…We identified 4 types of MALToma lesions, and the nodular ones were the most common (44.44%). This finding is in contrast with previous reports showing that the most frequent presentation was the consolidated type or diffuse interstitial lung disease 9,12,20–23 . Moreover, 3 of the 8 nodular lesions in our study were GGNs, rarely reported before.…”
Section: Discussioncontrasting
confidence: 99%
“…As illustrated by this case, the diagnosis of PPL rests on pathologic findings, thus further emphasizing the importance of prompt transbronchial or transthoracic needle biopsy in suspected cases. Immunohistochemical analysis contributes to the differential and positive diagnosis of MALT-type PPL [9]. The interval between the first clinical or radiological manifestation and diagnosis ranges from 5 months to 8 years.…”
Section: Discussionmentioning
confidence: 99%